Hospitality Business’ Attention to Food Safety and Hygiene - Ale, Saubhagya; Aryal, Sunita; Pudasaini, Achyut (International Journal of Atharva, 2023)
Food Safety and hygiene in hospitality establishments is to provide an overview of the importance of food safety and hygiene in the hospitality industry. This research used a quantitative survey to determine food safety and hygiene and HAACP in hospitality establishments in Kathmandu. The findings suggest a positive attitude towards food safety practices among the respondents, indicating a commitment to ensuring the health and well-being of both customers and food handlers in hospitality establishments. Improving food safety practices requires a collective effort from stakeholders, including owners, managers, and staff members, to create a culture of food safety.